Isocyanate dermal exposure among car spray painters in Kota Bharu, Kelantan - Amjn, Amirul Rosle (Universiti Sains Malaysia, 2016)
The main route of exposure for isocyanate is via inhalation but an alternative route that can contribute to sensitisation and asthma is also by skin exposure. This cross sectional study design is aimed to determine the association between isocyanate skin exposure and respiratory symptoms among car spray painters. A total of 11 car spray painters were recruited utilising purposive sampling method from five medium sized auto body workshops in Kota Bharu, Kelantan. SWYPE™ sampling pads was used to detect the isocyanate contamination on work surfaces (workbenches, container caps, spray gun and spray booth door handles), shoes and skin (hands and forehead) of car spray painters after painting task. The subjects were interviewed using guided questionnaire gathering sociodemographic, work and respiratory symptoms information. Majority of area hard surfaces wiped at the auto body workshops showed positive colour changes (66%, n=29) indicating presence of isocyanate contaminations. Skin isocyanate contamination showed higher frequencies on both hands (72.7%, n=8) than on the forehead. Six (54.5%) car spray painters was found had isocyanate contamination on their shoes. There was no significant correlation of isocyanate on the hard surfaces toward skin contaminations, but positive significant correlation between container caps and workbenches contamination (r=1.000, p<0.01 ). The association between skin and shoes contaminations with respiratory symptoms was found that only phlegm at morning was significant (p=0.024). SWYPE™ can serve as an important tool for detection of isocyanate dermal exposure routes towards respiratory symptoms. Preventive measures such as personal protective equipment (gloves and respirators) and hygiene practices are highly recommended to minimise isocyanate skin exposures among car spray painters.